PENGARUH MOTIVASI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN BARANG DISKON PADA MAHASISWA UTS DI MINIMARKET SUMBAWA BESA - FITRA HASRI ROSANDI; NINIK NURLATIFAH (Jurnal TAMBORA, 2022)
Consumer motivation is an impulse that comes from the ego to make a movement so that what is desired can be achieved. The purpose of this study was to determine the effect of consumer motivation on the decision to purchase discounted goods on UTS students at the Sumbawa Besar minimarket. This study uses a quantitative approach. The sampling technique used cluster sampling. The sample in this study amounted to 362 students. The research data was obtained using research instruments in the form of two scales, namely the consumer motivation scale and the purchasing decision scale. The results showed that consumer motivation had an effect on purchasing decisions with the value of Sig. 0.000 (Sig. <0.05) and R Square of 0.376, which means the higher the consumer's motivation, the higher the purchase decision. Consumer motivation has an effect of 37.6% and 62.4% is influenced by other variables outside the study. Consumer motivation in the good category with the highest aspect is the emotional aspect. Meanwhile, purchasing decisions are in the good category with the highest aspect being the rational aspect.